On the limits operators of \(q\)-King type sequences of operators - Finta, Zoltan (Modern Mathematical Methods, 2026)
We determine the limit operators for a sequence of generalized \(q\)-King operators and the sequence of \(q\)-Aldaz-Kounchev-Render operators. For each sequence of operators we prove the uniform convergence to the corresponding limit operators, for which we provide quantitative estimates.